Donne all’alba del nuovo millennio: dalla rivendicazione dei diritti all’affermazione dei doveri riproduttivi - Pompili, Anna (Il sogno della farfalla, 2020)
During the XXth century, women’s movement and civil society fought for the recognition of gender equality and reproductive rights. This led to relevant resolutions and to the approval of important laws both at a national and international level. Among them the first laws recognizing abortion as legal were adopted. Nowadays, at the beginning of the XXI century, these rights are undermined as are progressively becoming threatened: women are considered human beings only because of their ability to procreate. This is seen as the only possible realization for their identity. However, the reasons of this throwback were already concealed in the principles which inspired abortion laws. In these legislations, we can read the impossibility to act a real separation from the culture that sees in women’s natural irrationality the reason of their inferiority.